Pengaruh Likuiditas, Struktur Aktiva, dan Kebijakan Deviden terhadap Struktur Modal - Febriani Ayuningtyas, Ika; Purwanti (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: To determine the effect of liquidity, asset structure, dividend policy on capital structure either partially or simultaneously. Background Problems: It is the company's management in determining how it should meet the funding requirements to achieve an optimal capital structure. Novelty: Re-testing the same variables in previous studies with different companies and years. Research Methods: Using secondary data that is quantitative in the form of financial reports from manufacturing companies listed on the Indonesia Stock Exchange, as well as samples taken of 19 companies. Finding/Results: Partially, liquidity and asset structure have a significant negative effect on capital structure, dividend policy has a significant positive effect on capital structure, and simultaneously can have a significant effect on the value of capital structure. Conclusion: Asset structure and dividend policy can be used as a consideration for managers in making decisions regarding the optimal use of capital structure.